Hepatocellular carcinoma with disseminated skeletal muscle metastasis - Abdul Rahim, Ezamin; Md Noh, Mohamad Syafeeq Faeez; Ngah, Nur Aimi; Mohamad Saini, Suraini; Mohd Yusof, Mubarak (Sage Publications, 2017)
Hepatocellular carcinoma (HCC) is the commonest primary tumor of the liver and carries a poor prognosis when diagnosed late or left untreated. Treatment relies heavily on the stage of the tumor when diagnosed. Extrahepatic metastasis is known to occur; these are mainly reported via autopsy studies or isolated case reports. Knowledge of extrahepatic metastasis is crucial in order to avoid unnecessary surgery. We report a rare case of a patient at our center, diagnosed to have HCC, who underwent treatment successfully, only to come back with extrahepatic metastasis to the skeletal muscles.